Mag-aabroad ka ba? application at employment manual ng overseas workers - Bermillo, Edmundo Dacara ([S.l.] Verbena Pub., 1990)
This book contains both illustrated and written information for workers who are desiring to be employed abroad which provides them an insight into the recruitment, hiring and deployment processes starting from their application for employment to the post-employment stage and finally when they return home for good or for renewal of their contract.
Contents: "A detailed and comprehensive manual covering the requirements and technicalities of application process for overseas job, returning home and renewal of contract."
Purpose: "A sincere effort to present to the overseas worker as much as humanly possible an exhaustive and comprehensive application and employment manual."
Fi-9905g donated by Prof. Mamoru Tsuda, M.A., U.P., 1977.
Keywords: Employment in foreign countries -- Handbooks, manuals, etc